A THEORETICAL EXAMINATION OF OPPORTUNITIES AND CHALLENGES IN GREEN MARKETING WITHIN THE INDIAN MARKET CONTEXT. - A. V., Subeesh; T., Shenbhagavadivu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Green has become a global focal point, leading to heightened awareness of ecological threats that impact everyone’s lives. As a result, individuals are increasingly embracing a sustainable lifestyle, which has spurred demand for environmentally friendly products and services. Many business organizations are recognizing the importance of sustainability and are beginning to implement green marketing strategies. In today’s globalized and competitive landscape, green marketing proves to be highly effective. It aids in enhancing an organization’s image, attracting a larger consumer base, minimizing government scrutiny, and reducing interference from various environmental protection NGOs, thereby ensuring long-term business viability. Despite its numerous advantages, green marketing remains in its early stages in India. This paper aims to introduce the concept of green marketing, emphasizing the benefits of adopting such strategies within businesses. Additionally, it identifies the challenges faced in implementing green marketing and assesses the current state of green marketing in the Indian market.